A Methodological Framework for Airport Outbound Passenger Flow Modelling - Edrissi, Zineb; Bouksour, Otmane; Beidouri, Zitouni (International Journal of Supply Chain Management, 2020)
The airport is a logistics hub that handles several flows, including passengers flow. In fact, passengers are the common customer of all the actors of the airport chain. Thus, and considering growth of passenger air traffic, airport managers must find rational solutions with optimal use of available resources and infrastructures; hence the opportunity for a modeling study and an optimization of passenger circuits. This article took the initiative of presenting the passenger flow model with a holistic approach starting from airport access to the boarding gate and following, for the first time, a confirmed methodological framework which is the ASDI methodology (Analysis, Specification, Design and Implementation). This methodology relies on a system decomposition in three subsystems: SSP physic, SSL logic and SSD decision-making. Our study was conducted on Mohammed V International Airport of Casablanca, the first airport in Morocco, by building its generic model of knowledge of the flow of departing passengers; a model that can be reused and reproduced on other circuits, even other airports.